2021
DOI: 10.3934/ctr.2021001
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun nanofibers for efficient adsorption of heavy metals from water and wastewater

Abstract: <abstract> <p>Heavy metals (HMs) are persistent and toxic environmental pollutants that pose critical risks toward human health and environmental safety. Their efficient elimination from water and wastewater is essential to protect public health, ensure environmental safety, and enhance sustainability. In the recent decade, nanomaterials have been developed extensively for rapid and effective removal of HMs from water and wastewater and to address the certain economical and operational challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 217 publications
0
16
0
Order By: Relevance
“…Furthermore, the nanofibers' limited mechanical stability and reusability hinder their capability to be used in the large-scale water and wastewater treatment. Hence, there is a need for developing advanced technological solutions to improve the physical and chemical performances of nanofibers [53][54][55]. The suggestions for future works are as follows: (1) Further improvement of the stability, mechanical strength, and reusability of nanofiber membranes by means such as adjustment of the compositions of polymer solutions or water-insoluble polymer solutions; (2) Design and application of nanofiber membrane reactor in dynamic adsorption membrane chromatography.…”
Section: Remarks On Protein Modified Nanofiber Membrane For Dye Waste...mentioning
confidence: 99%
“…Furthermore, the nanofibers' limited mechanical stability and reusability hinder their capability to be used in the large-scale water and wastewater treatment. Hence, there is a need for developing advanced technological solutions to improve the physical and chemical performances of nanofibers [53][54][55]. The suggestions for future works are as follows: (1) Further improvement of the stability, mechanical strength, and reusability of nanofiber membranes by means such as adjustment of the compositions of polymer solutions or water-insoluble polymer solutions; (2) Design and application of nanofiber membrane reactor in dynamic adsorption membrane chromatography.…”
Section: Remarks On Protein Modified Nanofiber Membrane For Dye Waste...mentioning
confidence: 99%
“…Thus, there is a great need for researchers to develop effective technology in wastewater purification [35]. The main strategies in wastewater treatment may include filtration, adsorption, catalysis, centrifugation, biological treatment, and electro-coalescence [87]. More than 200 natural and synthetic polymers were successfully electrospun into nanofiber membranes, such as polyimide (PI), polyacrylonitrile (PAN), poly/vinyl alcohol (PVA), poly/vinylidene-fluoride (PVDF), polylactic acid (PLA), cellulose acetate (CA), polyurethane (PU), polyethylene oxide (PEO), and polycaprolactone (PCL) [35].…”
Section: Nanofibers For Water/wastewater Treatmentmentioning
confidence: 99%
“…Finally, electrospinning is an advanced shaping technique, which has been used to structure microporous framework materials either into 1D fiber structures or their more complex 3D variations for a broad range of applications, such as biomedical applications, air filtration, catalytic applications, water treatment and gas separation processes. As an example, in gas adsorption processes hierarchical porous zeolite nanofiber structures can reduce pressure drop and improve the diffusion of molecules. , However, the zeolite particles are usually embedded in the nanofiber polymer matrix after electrospinning. It has been shown that the coverage of the zeolite surfaces with the polymer often leads to a significantly reduced surface area and accessible pore volume, resulting in significantly lower gas uptake.…”
Section: Introductionmentioning
confidence: 99%